2018
DOI: 10.33202/comuagri.503835
|View full text |Cite
|
Sign up to set email alerts
|

Çanakkale İli Meyve Alanlarında Elma İçkurdu Cydia pomonella (L.) (Lepidoptera: Tortricidae)’nun Yayılışı Üzerine Bir Araştırma

Abstract: Elma iç kurdu Cydia pomonella (L.) (Lepidoptera: Tortricidae) başta elma (Malus domestica) olmak üzere armut (Pyrus communis), ayva (Cydonia oblonga) ve ceviz (Junglas regia) bahçelerinde önemli zararlara sebep olmaktadır. Çanakkale ili bu meyve türlerinin yetiştiriciliği açısından nitelikli bir tarımsal üretim merkezidir. Çalışmanın amacı, Çanakkale ilindeki meyve alanlarında zarar yapan elma içkurdunun yayılış alanları ve bulaşıklık oranlarının meyve esaslı metoda gö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Aydar et al (2007) reported that the infestation rate was reached to 74.15% in the control plot without chemical application in Eğirdir (Isparta) district conditions. Kuyulu and Genç (2018), found the level of codling moth infestation between 5% and 95%, in their study on the spread of codling moth in apple orchards in Çanakkale province…”
Section: Infestation Rates Of Codling Mothmentioning
confidence: 98%
“…Aydar et al (2007) reported that the infestation rate was reached to 74.15% in the control plot without chemical application in Eğirdir (Isparta) district conditions. Kuyulu and Genç (2018), found the level of codling moth infestation between 5% and 95%, in their study on the spread of codling moth in apple orchards in Çanakkale province…”
Section: Infestation Rates Of Codling Mothmentioning
confidence: 98%
“…Larvae feed on the fruit directly, creating spiral galleries towards the seed chamber of fruit and severely effects quality of fruit by feeding in the mesocarp of the apple and in the kernel (Beers et al, 2003;Öztemiz et al, 2017). Without any plant protection measures, damage may reach 60-95% of apple production (Kuyulu and Genç, 2018). Additionally, codling moth larvae feed on several plant species belonging to various families, including as peaches (Prunus persica L.), pears (Pyrus sp.…”
Section: Introductionmentioning
confidence: 99%